High School Online Science Education: Its Application and Perceptions during COVID-19 in American Curriculum Schools in the UAE. - GHAITH, FARAH (2023)
The COVID-19 pandemic has had a significant impact on education, with many schools and universities shifting to online learning as a way to continue instruction while maintaining social distancing guidelines. To gain a deeper understanding of online science education, this study focuses specifically on teachers’ and leaders’ perceptions of online science education during Covid-19. With the collected data, the study was able to identify the difficulties that teachers and leaders faced while teaching science online. This research followed a mixed approach in which a questionnaire was used to collect data from 21 high school educators teaching science in American schools in the UAE to identify their perceptions of online science education (Quantitative). In the other tool, 3 science leaders and 4 science teachers were interviewed to explore their perceptions on the application of online science education (Qualitative). Based on the results of this research, it can be inferred that the effectiveness of science education during the Covid-19 pandemic was not as high as traditional in-person education. There is a need for improvement in terms of curriculum, teaching strategies, and resources for online science education. Future research should expand to include a larger number of schools, educators, and curricula in order to gain a more comprehensive understanding of online science education.